항공기용 착륙장치 핸들의 진동 특성 개선에 관한 연구 - 강구헌(Gu Heon Kang); 안종무(Jong Moo Ahn) (항공우주시스템공학회지, 2018)
The landing gear (L/G) handle of an aircraft is an essential piece of equipment for aircraft take-off and landing. The bracket in the landing gear handle was fractured during a vibration test when developing the landing gear handle. This paper summarizes the vibration test procedures performed during landing gear handle development. A cause analysis, design improvements, and verification results of the fault in the vibration test are also provided. 항공기 구성품인 착륙장치 핸들은 항공기 이 착륙 시 착륙장치 작동을 위한 핵심적인 장비이다. 착륙장치 핸들의 개발을 위한 진동시험 중 착륙장치 핸들 내부의 브라켓 파손 현상이 발생하였다. 따라서 본 논문에서는 착륙장치 핸들 개발 시 수행한 진동시험 절차와 진동시험 중 발생한 결함사항에 대한 원인 분석, 설계 개선사항 그리고 검증 결과를 함께 기술하였다.